Avoidance of tolerance and lack of rebound with intermittent dose titrated transdermal glyceryl trinitrate. The Transdermal Nitrate Investigators. Issue 2 (August 1991) - Fox, K M; Dargie, H J; Deanfield, J; Maseri, A
Abstract : OBJECTIVES--To investigate the efficacy of transdermal glyceryl trinitrate given continuously and with a nocturnal nitrate free period. DESIGN--Double blind placebo controlled study with two parallel limbs. SETTING--Multicentre trial. PATIENTS--52 patients randomised to receive either continuous treatment (23 patients) or intermittent treatment with an individually titrated dose (29 patients) for 14 days: both treatments were compared with placebo in a cross-over fashion. INTERVENTION--Continuous treatment with 10 mg per 24 hours of transdermal glyceryl trinitrate or intermittent transdermal glyceryl trinitrate titrated to give an arbitrary 10 mm Hg drop in systolic blood pressure (mean dose 18.2 mg) given over approximately 16 hours. MAIN OUTCOME MEASURE--Treadmill exercise stress testing and ambulatory monitoring of the ST segment after 14 days' treatment. RESULTS--After 14 days' intermittent treatment resting supine and standing systolic blood pressure fell by 7.5 mm Hg (95% confidence interval 2.7 to 12.2) and 9.0 mm Hg (95% CI 3.4 to 14.5) respectively (p less than 0.01); resting heart rate was unchanged. Mean heart rate at 1 mm ST segment depression rose by 11.9 beats/min (CI 1.1 to 23.7) (p less than 0.05), mean time to onset of angina increased by 59 seconds (CI 10.8 to 108) (p less than 0.05), and total exercise duration increased by 40 seconds (p less than 0.05). These changes were not seen after continuous treatment. The frequency of ischaemic episodes was not reduced with either regimen nor was the circadian distribution of these episodes altered, in particular nocturnal episodes did not increase during intermittent treatment. CONCLUSION--Tolerance to glyceryl trinitrate was avoided by the use of individually titrated doses administered with a nocturnal nitrate free period. There was no evidence of "rebound" on ambulatory monitoring during this treatment.